AN ANALYSIS OF TECHNICAL DEVICES IN TRANSLATION PROCEDURES APPLIED IN HARRY POTTER FIRST NOVEL - Lina, Marisa Fran (LET: Linguistics, Literature and English Teaching Journal, 2018)
There are four technical devices in the translation procedures which are commonly used by the translator; addition, subtraction, adaptation and elimination. Thus, the purpose of this study are to find the four technical devices in Listiana Srisanti?s translation result in ?Harry Potter and the Sorcerer?s Stone?. The method of collecting data is library research. The data in the novel which have been collected are analyzed by the four technical devices. According to the classification, it is found that there are 10 data of addition, 13 data of subtraction, 12 data of adaptation and 9 data of elimination. Those data presented are representative enough from all of the data in the novel, because the writer takes the data by its part among the translated sentences contained the technical devices. In conclusion, the result shows that the technical device of subtraction is the most dominant data (13) applied in the novel.